Design of a Quick Response Code-Based Infrastructure Management Information System - Sukron, Moh.; Ramadhan, M. Raihan; Sihabillah, Ahmad (International Journal of Engineering and Computer Science Applications (IJECSA), 2024)
The management of infrastructure and facilities at MTs Mambaul Hasan Sumberrejo Paiton Probolinggo is currently conducted manually, resulting in significant issues such as data inaccuracies, misplacement of items, and difficulties in tracking asset movements. These challenges reduce efficiency and hinder effective inventory management. The aim of this research is to design and develop a Quick Response (QR) Code-based management information system to enhance the efficiency and effectiveness of infrastructure and facilities management at MTs Mambaul Hasan. This research method is based on Research and Development (R&D) with a quantitative approach and a case study framework. The process includes system requirements analysis through direct observation and interviews with school staff, followed by system design using the Object-Oriented Analysis and Design (OOAD) approach. A prototype is then developed and tested to gather user feedback, and system evaluation is conducted to refine the system before full implementation. The results of this research are a QR Code-based infrastructure and facilities management information system that simplifies asset registration, enhances tracking accuracy, and reduces manual workload. Usability testing with school staff revealed an 82,67% satisfaction rate, indicating a significant improvement in efficiency and traceability of assets. The implementation of this system provides a practical and effective solution for managing infrastructure and facilities at MTs Mambaul Hasan. This study concludes that the QR Code-based system improves efficiency, accuracy, and traceability in inventory management. The implications of these findings suggest that other educational institutions can adopt similar technological solutions to modernize their management processes, with potential future integration of mobile and cloud technologies for enhanced usability and scalability.